MENINGKATKAN KETERAMPILAN MENULIS SISWA DENGAN MENGGUNAKAN MODEL PROJECT BASED LEARNING DI KELAS XII IPA 1 SMA N 7 PADANG - Daswita Daswita (Menara Ilmu, 2020)
The aims of class action research is to solve the problem in limitations of student writing through the Project Based Learning model. The study was conducted in three cycles with six meetings. The research participatns were students of class XII Science 1 of SMA N 7 Padang in the odd semester of the 2019/2020 school year. Analysis of each cycle was based on test results to see cognitive abilities and non-test results observe activities and attitudes. Data were analyzed by using comparative descriptive techniques. The research findings showed an increase, both test results and non-test results. The percentage of completeness of the results onf the first cycle 50%, second cycle 71.9%, and third cycle 87.5%. Meanwhile, the non-test results revealed an increase in each cycles. Thus, it can be concluded that the use of Project Based Learning models is effective in improving students' writing skills. Keywords: writing skills, project based learning